Sleeping With the Enemy? The Current Knowledge of Piscine Orthoreovirus (PRV) Immune Response Elicited to Counteract Infection - Vallejos-Vidal, Eva; Reyes-López, Felipe E.; Sandino, Ana María; Imarai, Mónica (Frontiers in Immunology, 2022)
Piscine orthoreovirus (PRV) is a virus in the genus Orthoreovirus of the Reoviridae family, first described in 2010 associated with Heart and Skeletal Muscle Inflammation (HSMI) in Atlantic salmon (Salmo salar). Three phases of PRV infection have been described, the early entry and dissemination, the acute dissemination phase, and the persistence phase. Depending on the PRV genotype and the host, infection can last for life. Mechanisms of immune response to PRV infection have been just beginning to be studied and the knowledge in this matter is here revised. PRV induces a classical antiviral immune response in experimental infection of salmonid erythrocytes, including transcriptional upregulation of ifn-α, rig-i, mx, and pkr. In addition, transcript upregulation of tcra, tcrb, cd2, il-2, cd4-1, ifn-, il-12, and il-18 has been observed in Atlantic salmon infected with PRV, indicating that PRV elicited a Th1 type response probably as a host defense strategy. The high expression levels of cd8a, cd8b, and granzyme-A in PRV-infected fish suggest a positive modulatory effect on the CTL-mediated immune response. This is consistent with PRV-dependent upregulation of the genes involved in antigen presentation, including MHC class I, transporters, and proteasome components. We also review the potential immune mechanisms associated with the persistence phenotype of PRV-infected fish and its consequence for the development of a secondary infection. In this scenario, the application of a vaccination strategy is an urgent and challenging task due to the emergence of this viral infection that threatens salmon farming.